The Man on Devil's Island: Alfred Dreyfus and the Affair That Divided France - Harris, Ruth (United Kingdom Penguin Books Ltd, 2011)
This title is the winner of the Wolfson History Prize 2010 and the 2010 National Jewish Book Award for Biography. Ruth Harris writes beautifully and engagingly on a moment in French history that polarized society and undermined the French state; the repercussions of which were felt up to the outbreak of the Second World War. At the end of September 1894 a charlady stole an undated and unsigned letter from the wastepaper bin of the German military attache in Paris. Torn to pieces but stuck back together by French intelligence, this document contained French military secrets. By the middle of October a Jewish captain in the army called Alfred Dreyfus was accused of being its author. As it turned out, he was entirely innocent, but at the time few questioned the verdict of the subsequent court martial, nor the unanimous decision to sentence him to a life of penal servitude. Public opinion was outraged, and the War Minister, General Auguste Mercier, asked for the reintroduction of the death penalty so Dreyfus could be guillotined. Although the request was turned down, Dreyfus was still subjected to special conditions: rather than going to New Caledonia like other transported convicts, he was sent to the much harsher Devil's Island off the coast of French Guiana, and condemned to solitary confinement in murderous conditions. The French authorities did not expect - and probably did not want - him to survive. So undisputed was Dreyfus' conviction that no one had any inkling it would be queried, let alone that the case would become the scandal that nearly brought down the French state. It changed the political course of the nation and transformed the way the country viewed itself and was viewed by others.
France; c 1800 to c 1900
Biography: historical, political & military; European history; Modern history to 20th century: c 1700 to c 1900
Paperback
Keywords: Biography: historical, political & military